BUTTERFLY DIVERSITY OF CHRISTIAN COLLEGE CAMPUS, KATTAKADA, THIRUVANANTHAPURAM (INDIA) - A PRELIMINARY STUDY - KARIM, L. RAZEENA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
The present survey was aimed to prepare a checklist of the butterflies found in and around Christian college campus since this was the first study to check the butterfly fauna of the college. Butterfly survey revealed the presence of more than 100 butterflies belonging to 20 different species from six families. The dominant species belongs to the Family Nymphalidae with six species. Studies on the abundance of butterfly species at Christian College, Kattakada showed that 45% are very common, 30% rare, 10% belongs to Common and 15% belongs to Not rarecategory.